Performance leadership [ the next practices to motivate your people, align stakeholders, and lead your industry - Buytendijk, Frank (New York : McGraw-Hill, 2009)
Take your business to the next level in performance management-Performance Leadership
1. A review of performance management and what's wrong with it -- 2. Practical improvements for the operational and analytical dimensions -- 3. Guiding principles from the values and social dimensions -- 4. Implementing the performance leadership framework
Title from PDF title page (viewed Jan. 11, 2009)
Includes bibliographical references and index
Keywords: Leadership; Organizational effectiveness -- Management; Performance -- Management